Effects of Renal Denervation vs Sham in Resistant Hypertension After Medication Escalation Prespecified Analysis at 6 Months of the RADIANCE-HTN TRIO Randomized Clinical Trial - Azizi, Michel; Mahfoud, Felix; Weber, Michael A.; Sharp, Andrew S. P.; Schmieder, Roland; Lurz, Philipp; Lobo, Melvin D.; Fisher, Naomi D. L.; Daemen, Joost; Bloch, Michael J.; Basile, Jan; Sanghvi, Kintur; et al. (JAMA Cardiology, 2022)
IMPORTANCE Although early trials of endovascular renal denervation (RDN) for patients with resistant hypertension (RHTN) reported inconsistent results, ultrasound RDN (uRDN) was found to decrease blood pressure (BP) vs sham at 2 months in patients with RHTN taking stable background medications in the Study of the ReCor Medical Paradise System in Clinical Hypertension (RADIANCE-HTN TRIO) trial.
CRIS-Team WoS Importer:2022-12-02